A Meta-Individual World Theory as an Integrative Trend in Personality Studies - Dorfman, Leonid (Current Progress in Arts and Social Studies Research Vol. 7, 2024)
Aims: The aim of the study is to establish the foundations, composition and structure of the meta-individual world as a kind of integrative theory in personality studies. Place and Duration of Study: The study was organized at Perm State Institute of Culture, Russia, between April 2023 and November 2024. Results: The integral theory of individuality developed by Wolf Merlin, a dual-system model. The meta-individual world theory is presented and described in this study. The term 'meta' has epistemic and ontological meanings. From an epistemic point of view, the meta implies both integral individuality and an outside world behind it. On the ontological level, the meta-individual world is concerned with everyday life. The integral individuality and its close social settings are considered System 1 and System 2, respectively. They influence each other so that a subsystem of one system appears in the other. Then, each system possesses dual qualities. One is “native” and another quality appears from the other system. This means each system is both recipient and hybrid. This explains how Systems 1 and 2 intersect. It is noted that Systems 1 and 2 have distinct variables. So, there is no logical contradiction between the systems. Duality and complementarity of the meta-individual world are examined. They serve as a basis for a structuralist account in which the multi-dimensionality of the meta-individual world emerges. They are domains and sub-domains. Individuality and social setting are present in each sub-domain but their composition, relations and interactions differ. To clarify, these sub-domains have received the following names: “authorship”, “possession”, “perspective-taking”, and “relatedness”. The sub-domains connect with each other and provide the integration of the meta-individual world. Attention is drawn to some perspectives, making further progress. Hereby, implications and limitations are supplemented. Conclusion: The results of the study of the meta-individual world have been summarized and further research has been outlined.